Factors affecting treatment adherence to atomoxetine in ADHD: a systematic review - Treuer T; Mendez L; Montgomery W; Wu SH (Neuropsychiatric Disease and Treatment, 2016)
Tamás Treuer,1 Luis Méndez,2 William Montgomery,3 Shenghu Wu4 1Neuroscience Research, Eli Lilly and Company, Budapest, Hungary; 2Eli Lilly de Mexico, Mexico City, Mexico; 3Global Patient Outcomes and Real World Evidence, Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia; 4Neuroscience Research, Eli Lilly Asia, Inc, Shanghai, People’s Republic of China Abstract: The purpose of this paper was to systematically review the literature related to research about the factors affecting treatment adherence and discontinuation of atomoxetine in pediatric, adolescent, and adult patients with attention-deficit/hyperactivity disorder (ADHD). Medline was systematically searched using the following prespecified terms: “ADHD”, “Adherence”, “Compliance”, “Discontinuation”, and “Atomoxetine”. We identified 31 articles that met all inclusion and exclusion criteria. The findings from this review indicate that persistence and adherence to atomoxetine treatment were generally high. Factors found to influence adherence and nonadherence to atomoxetine treatment in ADHD in this review include age, sex, the definition of response used, length of treatment, initial dose of treatment, comorbid conditions, and reimbursement. Tolerability was cited as an important reason for treatment discontinuation. More research is needed to understand those factors that can help to identify patients at risk for poor adherence and interventions that could improve treatment adherence early in the stage of this illness to secure a better long-term prognosis. Keywords: atomoxetine, treatment discontinuation, adherence, compliance, ADHD medication, relapse